Understanding the complexity of Miller-Fisher syndrome: a case report - Ramachandran Satheebai, Parvathy; Asokan, Anil Kumar; Somasekaran, Hari Krishnan; Sreehari, Sreedhanya; John, Novin C.; Nair, Arya R.; Chittathuparambil Gopalakrishnan, Gowtham Kishore; Eapen, Aby C. (International Journal of Research in Medical Sciences, 2024)
Miller-Fisher syndrome is a rare neurological disorder characterized by a clinical trial of ophthalmoplegia, ataxia and areflexia. It is a variant of Gullian Barrie syndrome. A variety of other symptoms and signs beyond the triad has been reported. Here we report a case of a 58-year-old male patient with atypical presentation of Miller-Fisher syndrome. He had a history of upper respiratory tract infection 3 weeks prior. After hospital admission, he abruptly developed unsteadiness while walking, diplopia and dysphagia. Clinical evaluation along with antiganglioside antibody made the diagnosis of Miller-Fisher syndrome. After immunotherapy was initiated, the patient improved gradually and later discharged to home. To diagnose a case of Miller-Fisher syndrome, a high index of clinical suspicion and ruling out other aetiologies should be made. Timely effective intervention either plasmapheresis or IV Immunoglobulin can completely reverse the symptoms.